Evidence for rare crop weeds of the Caucalidion group in Southwestern Germany since the Bronze Age: palaeoecological implications : dedicated to the memory of Gerhard Lang (1924-2016) - Rösch, Manfred (Vegetation history and archaeobotany, 2018)
The crop weed communities of dry calcareous soils are today very rare and endangered. In the first half of the 20th century this group was already in an advanced stage of disappearance, caused by the intensification of agriculture since the 19th century. Therefore, botanists only found these plants in a few regions with calcareous soils, obviously reflecting the geological conditions. But many archaeobotanical finds are in places where this species was never observed as a living plant and edaphic conditions seem to exclude it. In the western Lake Constance region floristic observations are lacking. Of Orlaya grandiflora, there is now proof from several pollen diagrams that this species did occur regularly and with high frequency in this region from the Late Bronze Age to the 19th century ad. Several other species of the Caucalidion are also reflected in the pollen record, but are less frequent, reflecting the ecological conditions triggered by agriculture; due to soil erosion, topsoils were thin, especially on slopes, with low water capacity, and low yields. The weeds with spiny fruits were distributed over long distances by migrating domestic animals. Pollen grains in high-resolution pollen profiles from the northern Black Forest and Allgäu, where these plants were not to be expected and were never observed, indicate a ubiquitous distribution of the Caucalidion between Late Bronze Age and early Modern Ages in Central Europe and adjacent regions, reflecting the tenuous situation of long-term extensive ard agriculture in hilly landscapes. More and better pollen diagrams and macrofossil studies would bring better evidence.